Influence of wing-tip substituents and reaction conditions on the structure, properties and cytotoxicity of Ag(i)– and Au(i)–bis(NHC) complexes. Issue 8 (8th February 2017) - Rieb, Julia; Dominelli, Bruno; Mayer, David; Jandl, Christian; Drechsel, Jonas; Heydenreuter, Wolfgang; Sieber, Stephan A.; Kühn, Fritz E.
Abstract : Sterically demanding N -substituents favour the syn conformation leading to increase in cytotoxicity. Abstract : The formation of different conformers of dinuclear silver(i ) and gold(i ) 1, 1′-(2-hydroxyethane-1, 1-diyl) bridge-functionalized bis(NHC) complexes with various wing-tip substituents (R = methyl, isopropyl and mesityl) has been investigated using multinuclear NMR spectroscopy and SC-XRD as well as DFT calculations. The ratio of anti / syn isomers strongly depends both on wing-tip substituents and the metal. Moreover, the reaction temperature plays a significant role during the transmetallation process for the ratio of gold(i ) conformers, which is further affected by purification procedures. All obtained Au(i )–bis(NHC) complexes have been applied in a standard MTT assay performed for screening the antiproliferative activity against human lung and liver cancer cells. Strong evidence for a significant influence of both wing-tip substituents and conformation on the cytotoxic properties of the applied complexes has been found.